已知(2010-a)的平方+(2009-a)的平方=1,则(2010-a)(2009-a)=

来源:学生作业帮助网 编辑:作业帮 时间:2024/07/29 17:16:47
已知(2010-a)的平方+(2009-a)的平方=1,则(2010-a)(2009-a)=
x){}K5 t5jysi;"":O;f¤mm)7DΆJnB`0)2#- Ib$A=c`2202ħVD)//}~'FH

已知(2010-a)的平方+(2009-a)的平方=1,则(2010-a)(2009-a)=
已知(2010-a)的平方+(2009-a)的平方=1,则(2010-a)(2009-a)=

已知(2010-a)的平方+(2009-a)的平方=1,则(2010-a)(2009-a)=
(2010-a)^2+(2009-a)^2=1
((2010-a)-(2009-a))^2+2*(2010-a)(2009-a)=1
1^2+2*(2010-a)(2009-a)=1
(2010-a)(2009-a)=0

(2010-a)(2009-a)=2021

(2010-a)^2+(2009-a)^2=1
((2010-a)-(2009-a))^2+2*(2010-a)(2009-a)=1
1^2+2*(2010-a)(2009-a)=1
(2010-a)(2009-a)=0
应该对